First report of Rhodnius neglectus (Hemiptera, Reduviidae, Triatominae) from the State of Acre, Brazil, and the Brazilian Western Amazon Region - Ramos, Leandro Jose; Souza Castro, Gabriela Vieira de; Souza, Janis Lunier de; Oliveira, Jader de [UNESP]; Rosa, Joao Aristeu da [UNESP]; Aranha Camargo, Luis Marcelo; Cunha, Renildo Moura da; Oliveira Meneguetti, Dionatas Ulises de (Soc Brasileira Medicina Tropical, 2018)
Introduction: This communication reports the occurrence of Rhodnius neglectus in the State of Acre, Brazil. Methods: An adult male R. neglectus specimen was collected from the Catuaba Experimental Reserve, which is located in the municipality of Senador Guiomard. Results: This increases the number of triatomine species reported from the State of Acre to eight and is also the first report of R. neglectus from the Brazilian Western Amazon Region. Conclusions: The occurrence of R. neglectus is alarming because even though the species is wild, it can invade and colonize human dwellings and peridomiciles, thereby increasing Chagas disease transmission.
Keywords: Rhodnius neglectus; Chagas disease; Western Amazon